Pembrolizumab plus Chemotherapy in Advanced Endometrial Cancer - Eskander, Ramez N.; Sill, Michael W.; Beffa, Lindsey; Moore, Richard G.; Hope, Joanie M.; Musa, Fernanda B.; Mannel, Robert; Shahin, Mark S.; Cantuaria, Guilherme H.; Girda, Eugenia; Mathews, Cara; Kavecansky, Juraj; et al. (The New England journal of medicine, 2023)
In patients with advanced or recurrent endometrial cancer, the addition of pembrolizumab to standard chemotherapy resulted in significantly longer progression-free survival than with chemotherapy alone.